Targeting protein–protein interactions in complexes organized by A kinase anchoring proteins - Calejo, Ana I.; Taskén, Kjetil (Frontiers in Pharmacology, 2015)
Cyclic AMP is a ubiquitous intracellular second messenger involved in the regulation of a wide variety of cellular processes, a majority of which act through the cAMP - protein kinase A (PKA) signalling pathway and involve PKA phosphorylation of specific substrates. PKA phosphorylation events are typically spatially restricted and temporally well controlled. A-kinase anchoring proteins (AKAPs) directly bind PKA and recruit it to specific subcellular loci targeting the kinase activity towards particular substrates, and thereby provide discrete spatiotemporal control of downstream phosphorylation events. AKAPs also scaffold other signalling molecules into multi-protein complexes that function as crossroads between different signalling pathways. Targeting AKAP coordinated protein complexes with high-affinity peptidomimetics or small molecules to tease apart distinct protein-protein interactions (PPIs) therefore offer important means to disrupt binding of specific components of the complex to better understand the molecular mechanisms involved in the function of individual signalosomes and their pathophysiological role. Furthermore, development of novel classes of small molecules involved in displacement of AKAP-bound signal molecules is now emerging. Here, we will focus on mechanisms for targeting protein-protein interaction, disruptors that modulate down-stream cAMP signalling and their role, especially in the heart.